2019
DOI: 10.1093/eurheartj/ehy835
|View full text |Cite
|
Sign up to set email alerts
|

Association between time of hospitalization with acute myocardial infarction and in-hospital mortality

Abstract: This is a repository copy of Association between time of hospitalization with acute myocardial infarction and in-hospital mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 36 publications
(44 reference statements)
2
19
0
Order By: Relevance
“…The high incidence and mortality of acute myocardial infarction have long threatened human health and longevity [1,4]. Treatments such as thrombolysis or percutaneous coronary intervention can result in severe MIRI [3,5]. As MIRI is predominantly caused by excessive production of ROS [42], an ROS-responsive drug delivery system would be an appropriate treatment strategy method to release drugs at the injury site and reduce drug accumulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The high incidence and mortality of acute myocardial infarction have long threatened human health and longevity [1,4]. Treatments such as thrombolysis or percutaneous coronary intervention can result in severe MIRI [3,5]. As MIRI is predominantly caused by excessive production of ROS [42], an ROS-responsive drug delivery system would be an appropriate treatment strategy method to release drugs at the injury site and reduce drug accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Reperfusion following thrombolytic or primary percutaneous coronary intervention is considered to be the most effective treatment [1,2]. However, an incidence of 10%-25% of recurrent AMI and a hospital mortality rate of 6%-14% in patients with myocardial ischemia-reperfusion injury (MIRI) has been reported [3,4]. Potential mechanisms for MIRI include inflammation, energy metabolism disorder, oxidative stress, and apoptosis [5].…”
Section: Introductionmentioning
confidence: 99%
“…Acute myocardial infarction (AMI) and post-infarction chronic heart failure (CHF) are the leading causes of mortality worldwide [1]. Despite advancements in therapy for AMI and CHF during the past decades, it is necessary to find new therapeutics to decrease the morbidity and mortality from AMI.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Mehta et al successfully revealed increased reperfusion with percutaneous coronary intervention (PCI) and significant reduction in PCI mortality but increased cost and a non-significant reduction in mortality overall amongst all treatment pathways. As we know, telemedicine is increasingly common due to the COVID-19 pandemic and many studies have shown the usefulness of a telemedicine system for the early diagnosis of acute myocardial infarction and consequent reperfusion time reduction 2 .…”
Section: Universitas Muhammadiyah Banten Indonesiamentioning
confidence: 99%